Government Policies with respect to an Information Technology Cluster in Bangalore, India. - Van Dijk, Meine Pieter (European Journal of Development Research, 2003)
The southern states in India have developed a strong reputation as a source of software development services, with Bangalore, the capital of Karnataka, having the strongest reputation of all. This article focuses on the following issue: what determines the competitiveness of an information technology (IT) cluster? The following questions will be addressed: How did Bangalore become an IT cluster? What is the role of the external environment and, in particular, of the national state and local governments for the development of this IT cluster? Will the Bangalore cluster benefit or suffer from the present recession in the IT industry in the US? Finally, what explains the success of an IT cluster?